Development of Mushroom hub in Sangrur (Punjab) through Farmer FIRST Programme - Singh, Kuldeep; Kumar, Pankaj; Sharma, Shivani; Singh, Dalbeer (Indian Farming, 2022)
Mushroom cultivation is an occupation that has potential to uplift the economic status of the farmers without the need of heavy capital investment but farmers are not harnessing its full potential due to lack of awareness and technical know-how. FFP team popularized the mushroom cultivation enterprise among the farmers in the project villages of Sangrur (Punjab). With the continuous efforts of PAU, Ludhiana scientists, a number of farmers have adopted mushroom cultivation. Findings clearly shows that mushroomfarmers are generating a remunerative additional income from the venture without investing much money. A large number of farmers in such proximal area transformed the villages into the hub of mushroom cultivation, which is capable of disseminating the technology to other area. Pioneer farmers from the project villages are also extending the knowledge and experience to other farmers through various mediums. Overall, FFP has proved effective in livelihood upliftment of the farmers and performed effectively to develop the farmer-tofarmer extension model by building the capacity of farmers as the opinion leaders.